Using Paragraph Graphic Organizer from Brainpop Web to Improve the Writing Ability of the Eleventh Grade Students of SMA Datuk Ribandang - Rahmawati, Rahmawati; Anugrawati, Nunung; Ariana (FKIP Unismuh Makassar, 2019)
This research aimed to find out whether or not the use of paragraph graphic organizer from Brain POP can improve the writing ability of the eleventh grade students of SMA Datuk ribandang. The subjects of this research consisted of 54 students and it was divided into 2 classes, 27 students for control classand 27 students for experimental class at the eleventh grade of SMA Datuk Ribandang. The method that was used by the researcher in this research was quasi-experimental design which involved two classes with different treatment, namely experimental class and control class. The instruments used for collecting data namely writing test. The result of the data indicated that, the use of graphic organizer from BrainPop is effective than conventional (free writing) technique in improving students’ writing ability. Graphic organizer from BrainPop helps to make easier for the students in improving their writing ability. It is proved by the hypothesis result where p value (0.000) is smaller than α value (0.05). And it is also proved by the mean score of pre-test and post-test in experimental class and control class. It shows that pre-test mean score in experimental class is bigger than control class both content (24.44 > 22.22), organization (20.55 > 20.37), language use (23.52 > 21.29) and Writing Ability (68.51 > 63.88). Then, post-test mean score in experimental class is bigger than control class both content (33.15 > 29.07), organization (28.88 > 27.78), language use (31.48 > 27.03) and writing ability (93.51 > 83.88).It means that graphic organizer helps the students in increasing their writing ability and also can be an effective tool used in the writing process.